2023
DOI: 10.1002/smtd.202300549
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for 3D Integration Using Plasma‐Enhanced Atomic‐Layer‐Deposited Atomically‐Ordered InGaZnO Transistors with Ultra‐High Mobility

Abstract: As the scale‐down and power‐saving of silicon‐based channel materials approach the limit, oxide semiconductors are being actively researched for applications in 3D back‐end‐of‐line integration. For these applications, it is necessary to develop stable oxide semiconductors with electrical properties similar to those of Si. Herein, a single‐crystal‐like indium–gallium–zinc–oxide (IGZO) layer (referred to as a pseudo‐single‐crystal) is synthesized using plasma‐enhanced atomic layer deposition and fabricated stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Kim et al reported a high mobility thin film transistor (TFT) of 114.3 cm 2 V −1 s −1 at a pseudo-single-crystal of In 2 O 3 -rich IGZO channel. 19 Yang et al obtained a mobility value of 60.7 cm 2 V −1 s −1 IGO TFT by controlling the crystallinity and orientation of indium oxide cubic (222) at 700 °C annealing temperature. 24 In addition, Magari et al reported an In 2 O 3 channel transistor of 139.2 cm 2 V −1 s −1 mobility by increasing the grain size of indium oxide using hydrogen doping.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al reported a high mobility thin film transistor (TFT) of 114.3 cm 2 V −1 s −1 at a pseudo-single-crystal of In 2 O 3 -rich IGZO channel. 19 Yang et al obtained a mobility value of 60.7 cm 2 V −1 s −1 IGO TFT by controlling the crystallinity and orientation of indium oxide cubic (222) at 700 °C annealing temperature. 24 In addition, Magari et al reported an In 2 O 3 channel transistor of 139.2 cm 2 V −1 s −1 mobility by increasing the grain size of indium oxide using hydrogen doping.…”
mentioning
confidence: 99%
“…Recently, the high field-effect mobility of indium-based multicomponent crystalline OS, such as IGZO (In–Ga–Zn–O), , IGO (In–Ga–O), and In 2 O 3 channel transistors, has been reported. Kim et al reported a high mobility thin film transistor (TFT) of 114.3 cm 2 V –1 s –1 at a pseudo-single-crystal of In 2 O 3 -rich IGZO channel .…”
mentioning
confidence: 99%
See 1 more Smart Citation